Magnetic, structural, and photocatalytic properties of ferrites mefe2o4 (me = ni, mn, zn), obtained by plasma method - Фролова, Лилия Анатольевна (Science-based technologies, 2020)
Spinel ferrites of transition metals have been attracting the attention of researchers for many years. Nanodispersed ferrites have specific optical, electrical, magnetic and catalytic properties. The magnetic properties of ferrites depend on the nature, composition, and concentration of cations. In this work, composite ferrites MeFe2O4 (Me = Zn, Ni, Mn) were synthesized by the plasma method. The main characteristics of the obtained samples were determined by X-ray phase analysis, vibration magnetometry, EPR spectroscopy, UV-VS spectroscopy. To study the influence of the cationic composition on the properties of ferrites, a simplex lattice plan was used, which requires a minimum number of experiments to study the influence of factors on the selected response functions. It was found that the obtained ferrite nanoparticles have a spinel structure. The lattice parameter depends on the cation content. The minimum values correspond to the double compositions of manganese-nickel ferrites. Magnetic properties, such as saturation magnetization and coercive force, vary considerably depending on the concentration of cations. The coercive force for all samples is of small importance. In addition, the saturation magnetization of MnFe2O4 is much higher than in other samples (Ms is 111.8 Emu/g for MnFe2O4, for ZnFe2O4 Ms = 3.94 Emu/g). The photocatalytic activity of the compounds was studied in the decomposition reaction of methylene blue, which was used as a model organic pollutant. The photocatalytic activity of ferrites increases with increasing number of Ni ions. The degree of degradation of methylene blue increases from 44% for MnFe2O4 to 96 % for Ni0.33Mn0.66Fe2O4 and Ni0.33Zn0.66Fe2O4 after 60 minutes of irradiation in UV light. The intensity of the EPR peak spectrum and the band gap energy correlate with each other. The degree of degradation of MB is inversely proportional to the band gap.